Naringenin restores colistin activation against colistin-resistant gram-negative bacteria in vitro and in vivo - Xu, Mengxin; Yao, Zhuocheng; Zhao, Yining; Shi, Shiyi; Sun, Yao; Feng, Luozhu; Zhou, Cui; Zhang, Xiaodong; Cao, Jianming; Zhou, Tieli (Frontiers in Microbiology, 2022)
Colistin is used as the "last line of defense" against multi-drug resistant Gram-negative bacteria (GNB). However, improper use of colistin may further lead to an increasing number of colistin-resistant (Col-R) strains worldwide, which greatly limits antibiotic treatment options. In this study, we investigated the antibacterial and antibiofilm activities of naringenin (NG) combined with colistin against Col-R GNB in vitro and in vivo. The checkerboard method and time-kill test showed that NG combined with colistin has better antibacterial activity (FICI < 0.5) compared to NG and colistin alone. Biofilm formation inhibition tests demonstrated that combining the two drugs could inhibit biofilm formation; scanning electron microscopy confirmed that the combination of the two significantly reduces the number of cells in the biofilm compared to the drug alone. The in vivo experiment showed that the combination of NG and colistin can improve the survival rate of the Galleria mellonella (G. mellonella) and reduce the microbial load in the mouse thigh infection model. Mechanistically, the combination of NG and colistin synergistically enhances the antibacterial activity and changes the permeability of the bacterial outer membrane. More importantly, cytotoxicity tests showed no cell cytotoxicity of NG in combination with colistin. In conclusion, our data revealed that NG combined with colistin exhibited good synergistic effects in vivo and in vitro, thus providing a new therapeutic option for clinical Col-R GNB infections.